Quantifying Greenhouse Gas Emissions through Financial Market’s Development in Tunisia: Empirical Evidence from Novel Dynamic ARDL Techniques - Karaca, Ali; Salman, Abdulrahman Khalid Bin; Oueslati, Tarek; Missaoui, Ibtissem (International Journal of Energy Economics and Policy, 2025)
This study investigates the impacts of financial development (FMD), GDP per capita (GDP), primary energy consumption (ENG), and trade openness (TO) on total greenhouse gas emissions (EQ) in Tunisia over the period 2000–2021. Using the ARDL approach, complemented by FMOLS, DOLS, and CCR estimators, the results indicate that financial development significantly reduces emissions, reflecting its role in financing green projects and fostering technological innovation. In contrast, GDP per capita and energy consumption exert a positive and substantial effect on emissions, highlighting the carbon-intensive nature of Tunisian growth. Trade openness has a limited short-term effect but contributes to emission reductions in the long term. The negative and significant error-correction coefficient shows a rapid adjustment towards long-term equilibrium. These findings emphasise that promoting sustainable finance, accelerating the energy transition, and implementing well-regulated trade policies are essential levers for mitigating emissions and enhancing environmental sustainability in Tunisia.